EDUCATION ON THE MANUFACTURE AND APPLICATION OF ORGANIC FERTILIZER IN LUWUK VILLAGE BANTEN - Yusnita, Ria; Anggita, Rendi; Sugiharto, Purwanto Bayu; Ramadhan, Atala Noval Setia; Kusuma, Jaka Wijaya; Hamidah, Hamidah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
Luwuk Village is a  village located in the Gunungsari district,  Serang regency. The vital agriculture in this village is melinjo.    Meanwhile,  animal husbandry, buffalo, goats, and chickens are the main attractions in this village. The purpose of this service is to empower the Luwuk Village community to utilize household waste,  livestock and agricultural waste that can be used as organic fertilizer.   Organic fertilizer is expected to reduce the consumption of chemical fertilizers and increase soil fertility. It can control plant-disturbing organisms to increase the production of melinjo, which is the primary commodity for the people of Luwuk Village.   The service method used is in the form of socialization and training in making organic fertilizers. The results achieved in the implementation of the service of the Application of   Appropriate  Technology for the  Manufacture of Organic Fertilizer in Luwuk Village,  Gunungsari District, Serang  Regency are (1) the community can take advantage of waste into fertilizer;(2) utilization of fertilizer from household organic waste for agriculture; (4) environmental cleanliness from organic waste. The benefits of this service activity are: (1) For lecturers, they can contribute their knowledge and thoughts to the community; (2) For people in the  Luwuk Village area,  Gunungsari District,   Serang Regency,  they can produce compost independently and relatively cheaply from the processing results organic waste as a support for the processing of agricultural processes and agricultural products